THE NATIONAL MEDIA AS A FACTOR IN THE FORMATION OF THE MODERN UKRAINIAN IDENTITY AND CONSOLIDATION OF THE SOCIETY - Гнатюк, С. Л. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The report looks upon the system of the national media in its influence on formation of the modern Ukrainian identity and consolidation of the society.